The Divine Feminine in the Song of Songs: A Comparative Mythological Analysis - Kotzé, Zacharias (Advances in ancient Biblical and Near Eastern research, 2025)
The elusive identity of the beloved in the Song of Songs has long intrigued interpreters. While the allegorical interpretation of the beloved as the people of Israel in the Judaic tradition or the bride of Christ in the Christian tradition is widely recognized, recent scholarship has increasingly explored her role as a representative of diverse female archetypes. Yet, an intriguing avenue remains only partially explored: the possibility of perceiving her as an embodiment of an ancient Near Eastern deity. This article investigates the presence of mythological elements within the character and actions of the beloved. Employing comparative hyleme analysis, it endeavours to illuminate the parallels between the beloved’s qualities and deeds and those of Inanna/Ishtar as chronicled in ancient Near Eastern literature.